APPLYING LEARNER – CENTERED TEACHING TO PROMOTE THE EFFECTIVENESS OF SPEAKING CLASSES FOR FIRST YEAR MAINSTREAM STUDENTS OF THE FACULTY OF ENGLISH LANGUAGE TEACHER EDUCATION, ULIS -VNU - Nguyen, Thi Thanh Xuan (2020)
English teaching style often causes a big trouble for both teachers and educators who are trying their best to help their students make the best use of English. The idea of teaching and applying new methods like learner-centered teaching has been mentioned for a long time but its effect in Vietnam educational system is not much. This study examines the effectiveness of applying learner-centered teaching in speaking lessons for first-year mainstream students of the Faculty of English Language Teacher Education, ULIS-VNU. The paper began by reviewing current trends of teaching speaking and related studies. The data was collected mainly through two class observations, the interviews with two speaking teachers and students’ survey questionnaire. Basing on the findings and observations in the study, the researcher proposed some suggestions to solve the existing problems and to improve the students’ learning and teachers’ teaching styles in speaking classrooms. Added to that, this research suggested some techniques which are expected to be helpful for teachers to carry out good lessons based on learner-centered teaching.